Hubungan Kadar Pb Udara, Kandungan Pb dalam Urine dengan Keluaran Maternal dan Neonatus Pada Pedagang Diterminal Tirtonadi Surakarta Tahun 2002. - Astuti, Sri Ratna; Setiani, Onny; Nurjazuli, Nurjazuli (Jurnal Kesehatan Lingkungan Indonesia, 2003)
ABSTRACT Background : The increasing number of motor vehicle in Central Java  has seriously brought the health effects to community because of the increasing pollution of the Lead (Pb) in the air. The objectives  of this research is to find the relationship between the content of the Lead (Pb) in the air, the content of the Lead (Pb) in urine with the outcome of maternal and neonatus of the sellers in the bus terminal Tirtonadi Surakarta, 2002. Method : This was an explanatory research using  cross sectional approach. The population of this research was all women who worked as sellers at the age of 20 - 40 years old. Thirty-one samples (total population) were taken. The measuring of the Lead (Pb) content in the air and urine were analyzed using AAS method. The interviewing of the respondents collected the outcome data of maternal and neonatus. The result analysis used the multiple-correlation test with significance level on 0,05 and used prevalence ratio. Result : Based on statistical analysis, it is known that the content of the Lead (Pb) in the air has significant relationship with the outcome of neonatus (p value < 0,05). The working duration has significant relationship with the health interference neonatus (p value < 0,05). The Lead (Pb) in the air is predicted as the risk factor for maternal outcome (RP > 1) and the Lead (Pb) in urine is predicted as the risk factor for neonatus outcome (RP > 1). Conclusion : There is a  significant relationship between the content of the Lead (Pb) in the air with the outcome of neonatus of the sellers in the bus terminal Tirtonadi in Surakarta, 2002. Key words   : Lead in the air, urine, maternal and neonatus outcome, sellers, bus  station.